Biomimetic bioreactor for potentiated uricase replacement therapy in hyperuricemia and gout - Yang, Bin; Luo, Guihu; Nie, Tailei; Ban, Zhenglan; Ning, Quanxin; Zhang, Jialin; Liu, Xiangru; Lin, Yanhua; Xie, Xiaochun; Chen, Qianyun; Zhong, Han; Huang, Ying; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionUricase replacement therapy is a promising approach for managing hyperuricemia and gout but is hindered by challenges such as short blood circulation time, reduced catalytic activity, and excessive hydrogen peroxide (H2O2) production. These limitations necessitate innovative strategies to enhance therapeutic efficacy and safety.MethodsWe designed and synthesized RBC@SeMSN@Uri, a red blood cell-coated biomimetic self-cascade bioreactor, which encapsulates uricase (Uri) and a selenium-based nano-scavenger (SeMSN) within RBC membranes. This design aims to reduce immunogenicity, extend systemic circulation, and maintain enzymatic activity. In vitro assays were conducted to evaluate biocompatibility, anti-inflammatory effects, and oxidative stress protection. In vivo experiments in hyperuricemia and gout models assessed therapeutic efficacy, biodistribution, and biosafety.ResultsRBC@SeMSN@Uri effectively degraded uric acid (UA) into allantoin and converted H2O2 into water, preventing oxidative damage and inflammation. In vitro assays demonstrated excellent biocompatibility and reduced H2O2-induced inflammatory responses compared to free uricase. In vivo, the bioreactor prolonged circulation time, significantly reduced uric acid levels, alleviated kidney damage, and mitigated symptoms of hyperuricemia and gout. It also targeted inflamed joints, reducing swelling and inflammation in gouty arthritis models.DiscussionThis study presents RBC@SeMSN@Uri as a novel biomimetic strategy for enzyme replacement therapy in hyperuricemia and gout. By integrating uricase and selenium-based nano-scavenger within RBC membranes, the bioreactor addresses key limitations of traditional therapies, offering enhanced stability, reduced immunogenicity, and superior therapeutic efficacy. This platform holds potential for broader applications in protein or antibody delivery for enzyme replacement therapies in other diseases.